Development of a candidate method for forensic microbial genotyping using multiplex pyrosequencing combined with a universal biotinylated primer. (January 2015) - Gu, Yan; Mao, Xuhu; Zha, Lagabaiyila; Hou, Yiping; Yun, Libing
Highlights: We develop a SNP genotyping method based on pyrosequencing for microbial forensics. Multiplex pyrosequencing combined with a universal primer serves as a rapid tool. The new pyrosequencing assay is cost-effective and reliable in SNP subtyping. E. coli O157 strains from 1504 Chinese livestock samples exhibit poor polymorphism. Abstract: Bacterial genotyping can be used for crime scene investigations and contribute to the attribution of biological attacks for microbial forensics. PyroMark ID Pyrosequencer as an accurate detection platform for single nucleotide polymorphisms (SNPs) has been applied to identify and resolve microorganisms involved in closely Escherichia coli O157:H7 ( E. coli O157:H7). To explore more applications and improve the efficiency for pyrosequencing in this field, we developed a method integrated multiplex pyrosequencing with a universal primer. Two multiplex pyrosequencing assays with a universal biotinylated primer were designed to analyze five SNPs located in four gene of E. coli O157:H7 strain. The accuracy of the established assays was validated by genotyping reference strain E. coli O157:H7 EDL933 and E. coli K-12. We also demonstrated that two multiplex pyrosequencing assays were specific and sensitive for genotyping closely related E. coli O157 strains. Reproducibility of results and multiplexing capability were evaluated by a comparison of this method with the monoplex pyrosequencing. Furthermore, these two multiplex pyrosequencing assays have been successfully applied to detect 11 E. coli O157 strains isolated from 1504 Chinese livestock samples. This method reduces costs and time consumption in the process of pyrosequencing analysis, and potentially serves as a rapid tool and reliable candidate strategy for the microbial identification and other genotyping application.